Greater than the sum of their parts: an overview of the AvrRps4 effector family - Horton, Katie N.; Gassmann, Walter (Frontiers in Plant Science, 2024)
Phytopathogenic microbes use secreted effector proteins to increase their virulence in planta. If these effectors or the results of their activity are detected by the plant cell, the plant will mount an immune response which applies evolutionary pressure by reducing growth and success of the pathogen. Bacterial effector proteins in the AvrRps4 family (AvrRps4, HopK1, and XopO) have commonly been used as tools to investigate plant immune components. At the same time, the in planta functions of this family of effectors have yet to be fully characterized. In this minireview we summarize current knowledge about the AvrRps4 effector family with emphasis on properties of the proteins themselves. We hypothesize that the HopK1 C-terminus and the AvrRps4 Cterminus, though unrelated in sequence and structure, are broadly related in functions that counteract plant defense responses.